Penerapan Pemberian Aromaterapi Lavender terhadap Penurunan Score Nyeri Post Sectio Caesarea di Ruang Rawat Inap - E. Dwi Aryani; Novita Anggraini; Bangun Dwi Hardika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Sectio caesarea is a surgical operation to help pregnant women give birth by making an incision in the abdominal wall (laparotomy) and uterus (hysterectomy). Non-pharmacology can be used together to relieve pain. Within 24 hours after a cesarean section, patients can feel a five-fold reduction in pain thanks to lavender aromatherapy. linalyl acetate, and linalool, which can have a calming effect. When lavender aromatherapy is inhaled, the compounds it contains trigger the hypothalamus to produce endorphins that can calm and soothe. the purpose of this study was to determine whether lavender aromatherapy can reduce the pain scale of post-Sectio Caesarea patients. This type of research is a one-shot case study,design with the application of Evidence Based Practice with 4 respondents. The intervention was carried out once a day for 2 consecutive days with a duration of 15 minutes. The results of this study showed a decrease in pain scores in the range of 2-0, so it can be concluded that the intervention of providing lavender aromatherapy can reduce the pain scale of post-Caesarean section patients. For post caesarean section patients they can apply lavender aromatherapy in pain management efforts.